Inhibition of breast cancer cell growth and migration through siRNA-mediated modulation of circ_0009910/miR-145-5p/MUC1 axis - Maryam Abtin; Nahid Nafisi; Asghar Hosseinzadeh; Sepideh Kadkhoda; Ramesh Omranipour; Leyla Sahebi; Masoumeh Razipour; Soudeh Ghafouri-Fard; Abbas Shakoori (Non-coding RNA Research, 2024)
Circular RNAs (circRNAs) characterize a novel kind of regulatory RNAs distinguished by great evolutionary conservation and constancy. Although their exact role in malignancies is not fully understood, they mainly work through specific axes. Circular RNA/miRNA/mRNA axes affect the pathogenesis of human cancers including breast cancer. We assessed the expression and function of circ_0009910/miR-145-5p/MUC1 axis in Breast Cancer tissues and MCF-7 cells. Expression levels of circ_0009910 and MUC1 were notably increased in breast cancer tissues compared with control tissues, parallel with the down-regulation of miR-145-5p. Clinicopathological analysis indicated that up-regulation of circ_0009910 in breast tumors is related to invasion of the tumor to lymph node (P value = 0.011). Also, the downregulation of miR-145-5p was significantly correlated with tumor invasion to lymph nodes (P value = 0.04) and HER2-negative tumors (P value = 0.037). Finally, overexpression of MUC1 was correlated with age under 45 years (P value = 0.002). More importantly, circ_0009910-siRNA decreased the proliferation and migration ability of breast cancer cells, enhanced expression of miR-145-5p, and decreased levels of MUC1. Taken together, the circ_0009910/miR-145-5p/MUC1 axis has been demonstrated to affect the pathogenesis of breast cancer and might provide a target for breast cancer treatment.